Pengaruh Kontrol Diri dan Konformitas Teman Sebaya Terhadap Perilaku Konsumtif Berbelanja Online pada Mahasiswa - Afisti, Eltasya; Sujadi, Eko; Ahmad, Bukhari (Guidance and counseling the university of Prof. Dr. Hazairin. SH, 2024)
Consumptive behavior in online shopping is a common practice among college students, despite its potential negative impacts across various aspects of their lives. This study aimed to describe the prevalence of online shopping consumptive behavior, peer conformity, and self-control among students. It also analyzed the influence of self-control and peer conformity on online shopping consumptive behavior. The research adopted a quantitative approach with a survey method. A total of 125 students, selected through convenience sampling, participated by completing the Self-Control Scale, Conformity Scale, and Consumptive Behavior Scale. Data were analyzed using simple and multiple linear regression techniques. The findings revealed that online shopping consumptive behavior was categorized as moderate, while self-control and peer conformity were categorized as high. Additionally, hypothesis testing confirmed that self-control and peer conformity had significant effects on students' online shopping consumptive behavior. These results highlight the importance of developing targeted guidance and counseling programs in higher education to prevent and address students’ consumptive behavior. Such programs should focus on enhancing students’ self-control and promoting positive peer interactions, thereby fostering a supportive social environment for effectively managing consumptive behavior.